Bibliometrics of the current state of application of teletechnology in the rehabilitation of patients with heart and large blood vessel disease - Wang, Sican; Yu, Ping; Zhou, Xuemei; Yuan, Yuan; Chen, Jian; Chen, Dongmei; Liang, Jingyan; Xu, Li (Frontiers in Medical Technology, 2025)
The first publication on the use of teletechnology in heart and large blood vessels dates back to 1961. Since then, the study of teletechnology in heart and large blood vessels has become popular, and the number of publications has drastically increased. Hence, it is imperative to establish a comprehensive research framework that enables researchers and other stakeholders to understand the use of remote technologies in heart and large blood vessels. To bridge this gap, bibliometrics was used, a novel approach to determine the most prolific countries, institutions, journals, authors, source topics, funding agencies, and the most popular category of remote technologies and solutions for disease rehabilitation. The corpus was extracted from the WOS core database and analyzed using CiteSpace 6.2R7 and VOS Viewer 1.6.18 versions. The number of publications has grown since the start of the 21st century, with the United States, the United Kingdom, and Italy being the most productive nations. The most commonly used remote technology was a 24 h dynamic electrocardiogram (ECG) and ambulatory blood pressure monitoring. The most researched objective indicators were heart rate, blood pressure, and cardiac output. The primary research focused on daily life, physical activity, exercise endurance, and quality of life. Moreover, heart failure and coronary artery disease were the most extensively researched diseases.